The The Role of Pikukuh Karuhun in the Decision-Making of Indigenous Communities in Daily Life: A Case Study of the Baduy Traditional Village - Surya Ningsih; Muhammad Hendri Nuryadi; Rima Vien Permata Hartanto (Journal of Citizenship, 2026)
This study aims to: 1) Analyze the implementation of Pikukuh Karuhun in the Baduy Indigenous Community's decision-making in everyday life. 2) Explain the indicators underlying Baduy Indigenous Community decision-making. This study uses a qualitative approach with a case study method. Data collection techniques include: 1) Direct observation conducted with informants, namely the Baduy Indigenous Community, who observed their daily character and behavior. 2) Interviews with two informants representing the Baduy community. 3) Documentation by conducting document searches referring to data collection from various written sources or relevant documents. Validity testing in this study used triangulation of methods and data sources. Data analysis used interactive data analysis techniques, namely data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that: 1) The Baduy community's decision-making in daily life reflects the strength of the Pikukuh Karuhun (root) system. 2) The structure of society influences how individuals make decisions. 3) Authority is an important determinant of Baduy community decision-making in daily life. Keywords: Pikukuh Karuhun, Baduy Tribe, Decision Making .